Preventable risk factors of dementia: Population attributable fractions in a Brazilian population-based study - Wyllians Vendramini Borelli; Vanessa Bielefeldt Leotti; Matheus Zschornack Strelow; Márcia Lorena Fagundes Chaves; Raphael Machado Castilhos (Elsevier, 2022)
Summary: Background: Knowledge regarding the modifiable risk factors of dementia is fundamental to guide public health policy. We aimed to estimate the population attributable fraction of modifiable risk factors of dementia among adults from a nationwide epidemiological study. Methods: We used the public database of the Brazilian Longitudinal Study of Aging (ELSI-Brazil) to calculate the Population Attributable Fraction (PAF) for ten risk factors, including education level, hearing loss, hypertension, alcohol consumption, obesity, active smoking, depression, social isolation, physical inactivity, and diabetes. PAF was estimated for this sample after accounting for the communality of each risk factor. Findings: The ten preventable risk factors for dementia accounted for 50·5% of the Population Attributable Fraction in Brazil. Hearing loss (14·2%), physical inactivity (11·2%), and hypertension (10·4%) accounted for the highest PAF among all the risk factors. Considerable variation in the relative contribution of the different risk factors was found in different regions. Interpretation: This study might provide an opportunity to change the impact of dementia in Brazil. By targeting modifiable risk factors of dementia, the health of individuals in Brazil might be considerably improved. Funding: This study did not receive any funding.